Knowledge, awareness and outlook on the COVID-19 disease among the dental professionals in Tamil Nadu - K S. Sethna Muth Lakshmi; C L Krithika; A Kannan; Yesoda Aniyan (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to analyze the knowledge, level of awareness, and the attitude of the dental professionals towards the pandemic disease (COVID-19). Materials and Methods: This questionnaire-based survey was conducted among 295 dental professionals residing in Tamil Nadu through an online portal. The questionnaire consisted of four sections that addressed the demographic data, knowledge, awareness, and outlook of the COVID-19 disease by dental professionals. All the received responses were tabulated and the results were represented graphically. Result: The result of the study showed significant awareness among dental professionals towards COVID-19. The dental professionals needed more attention towards the precautions to be followed during this pandemic as personal protection and a safe environment are essential for a secure practice. Conclusion: This study emphasizes the role of oral health professionals in the prevention of the transmission of coronavirus among the public along with the management of dental emergencies with appropriate personal protective measures. This study also enforced the need to enrich the knowledge about infection, transmission, prevention, and control towards COVID-19. This may act as a source of information for the future pandemic crisis.